Acceptability study of “Ascenso”: an online program for monitoring and supporting patients with depression in Chile - Espinosa Duque, Henry Daniel; Moessner, Markus (Telemedicine and e-health, 2016)
Background: Major depression is a highly prevalent and severe mental disease. Despite the effective treatment options available, the risk of relapse is high. Interventions based on information and communication technologies generate innovative opportunities to provide support to patients after they completed treatment for depression. Materials and Methods: This acceptability study evaluated the Internet-based program Apoyo, Seguimiento y Cuidado de Enfermedades a partir de Sistemas Operativos (ASCENSO) in terms of its feasibility and acceptability in a sample of 35 patients in Chile. Results: The study reveals high rates of acceptance and satisfaction among patients who actively used the program. As obstacles, patients mentioned technical problems, a lack of contact with other participants, and an insufficient connection between the program and the health service professionals. Conclusions: ASCENSO appears to be a promising complement to regular care for depression. Following improvements of the program based on participants' feedback, future research should evaluate its efficacy and cost-effectiveness.
Gesehen am 08.02.2018